Efektivitas Pasca Vaksinasi Hepatitis B di Kecamatan Pakal, Surabaya, Jawa Timur - William Sayogo; Wira Widjaya Lindarto; Cempaka Harsa Sekarputri; Jemina Lewi Santoso; Stefani Nurhadi; Ferdinand Aprianto Tannus; Inez Purnomasari Prajitno (Universitas Gorontalo, 2022)
Hepatitis is an infectious disease that is still a concern today and is at risk of becoming a chronic condition with complications of liver function failure. Screening is carried out to determine the level of response of the body's defense system induced by the vaccine in the population of Pakal district, Surabaya. This study assesses the relationship between antibody status and protection status after vaccination. The study involved 78 people who are eligible to receive the vaccine. After receiving the vaccine, the antibody status is checked and the data obtained were statistically tested and tested for association using a contingency coefficient. From 78 hepatitis B vaccine recipients, 69 people (88,46%) are antibody reactive and 9 people (11.54%) with non-reactive antibody status. From the Chi Square test and the contingency coefficient test, it is shown that there is a relationship between antibody status and protection status (α<0.05; 95% CI). The hepatitis B vaccine provides protection against the risk of hepatitis B virus infection for residents of the Pakal district of Surabaya who have a high-risk lifestyle.